UTILIZATION OF EYE TRACKING TECHNOLOGY IN DESIGN AND MARKETING DECISION MAKING - Mustikawan, Arry; Swasty, Wirania; Naufalina, Fariha Eridani (UI Scholars Hub, 2021)
Manuscript type: Original paper Research Aims: This study aims to reveal whether combination display affects fixation count and duration. Design/methodology/approach: This study used eye tracking methods in data collection and packaging design testing from the results of previous study. Respondents who participate were 40 people from teenagers and young adults. The collected data were analyzed quantitatively by the amount of fixation and processed by the Multivariate Analysis of Variance (MANOVA) test. Research Findings: From the statistical data on Baba Nana Brand, the average duration of the respondents did not show any difference in the study. However, the number of variables showed differences in the whole study. In other words, the respondent's gaze is quite a lot and often looks at the Baba Nana. It was revealed that the Baba Nana as a brand that is not yet on the market turned out to be quite attractive to respondents. Theoretical Contribution/Originality: Utilization of eye tracking technology in design and marketing decision making. Practitioner/Policy Implication: Marketers can utilize eye tracking technology in making design and marketing decisions, mainly when launch a new product to the market. Research limitation/Implications: Further research can study whether the fixation count and duration variable duration affects the consumer's statement of product interest.